Effective interventions for acquisitive offenders: an investigation of cognitive skills programmes - Wilson, Sally (Legal and criminological psychology, 2003)
Purpose. Previous research has suggested that cognitive skills programmes completed by offenders may be more effective in reducing reconviction with nonacquisitive than acquisitive offenders. This study investigates whether a similar pattern is present with offenders who have completed accredited cognitive skills programmes in prisons in England and Wales. Method. Questionnaires measuring the cognitive deficits targeted by the programmes were administered to 8,303 offenders participating in cognitive skills programmes while in custody. A checklist on the individuals' behaviour was also completed for each participant. The questionnaires and the behaviour checklist were completed before, after, and at 8 weeks after the end of the course. Participants were assigned to one of three groups dependent upon the number of convictions they had received for acquisitive offences; non-acquisitive, medium acquisitive and high acquisitive. Results. Offenders in the high acquisitive group showed greater need in the cognitive deficits at the pre-course stage than the other two groups, for both the self-completion questionnaires and the behaviour checklist. A comparison of preand post-course scores on the questionnaires and the behaviour checklist showed positive effect sizes for all three groups. Some of the variables showed a greater change from pre- to post-course in the groups that had been convicted of more acquisitive offences. Conclusion. Cognitive skills programmes appear to be as effective with offenders convicted of acquisitive crime as non-acquisitive crime, although highly acquisitive offenders may benefit from an additional intervention. Further studies are needed to investigate whether this same result is upheld when the outcome measure is reconviction.